The English connection : the Puritan roots of Seventh-Day Adventist belief - Ball, B. W. (Bryan W.) (Cambridge, United Kingdom : J. Clarke, 2014)
A historical study of 17th century Puritan theology, showing how many of its specific doctrines influenced the development of Seventh-Day Adventism. This book begins with a comprehensive history of Puritanism, emphasising its reliance on biblical exegesis and exposition, and the factors which contribute to collection of many strands.
The sufficiency of Scripture -- This incomparable Jesus -- The Lord our righteousness -- The new man -- Believer's baptism -- A high priest in heaven -- Gospel obedience -- The seventh-day Sabbath -- The whole man -- The return of Christ -- That great almanack of prophecy -- The world to come.
Includes bibliographical references.
Description based on online resource; title from PDF title page (EBSCO, viewed March 23 2015).
Keywords: Puritans -- England -- Doctrines -- History; Seventh-Day Adventists -- Doctrines -- History; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Puritans -- Doctrines; Seventh-Day Adventists -- Doctrines; England; Puritans -- Doctrines -- England -- Influence; Seventh-Day Adventists -- Doctrines -- History; RELIGION / Christianity / Protestant; Electronic books; History